Reflections on the IJHPR's article collection on dementia - Jill Harrison; Vincent Mor; Susan Mitchell; Ellen P. McCarthy (BMC, 2020)
Abstract Alzheimer's disease and Alzheimer's disease-related dementias (AD/ADRD) constitute a worldwide public health crisis. In light of the AD/ADRD epidemic now existing within the global COVID-19 pandemic, the need for global action to improve dementia care is greater than ever. The article collection "Dementia- an Interdisciplinary Approach," in the Israeli Journal of Health Policy and Research (IJHPR) highlights the need for interprofessional approaches to improving outcomes for people living with dementia and their care partners, as well as the complexities of conducting dementia care research.